The association of blood metals with latent tuberculosis infection among adults and adolescents - Wu, Jinyi; Wang, Kai; Tao, Fengxi; Li, Qingwen; Luo, Xin; Xia, Fang (Frontiers in Nutrition, 2023)
Objective We aimed to investigate the relationship of metal exposure and latent tuberculosis infection (LTBI) among US adults and adolescents.Methods Participants from the National Health and Nutrition Examination Surveys (NHANES 2011~2012) were included. Multiple logistic regression models were used to explore the associations between metal exposure and LTBI. A total of 5,248 adults and 1,860 adolescents were included in the present analysis.For adults, we only found a positive association between total mercury and LTBI (OR: 1.411; 95% CI: 1.164~1.710) when used as a continuous variable.Compared with Q1, Q4 increased the prevalence of LTBI (2.303; 1.455~3.644) when used as a quartile. The OR of total mercury and LTBI was higher among females (1.517; 1.009~2.279), individuals aged 45~64 (1.457; 1.060~2.002), and non-Hispanic White individuals (1.773; 1.316~2.388). A relationship was observed among only participants with obesity (1.553; 1.040~2.319) or underweight (1.380; 1.076~1.771), with college or above (1.645; 1.184~2.286), with PIR>3.0 (1.701; 1.217~2.376), reported smoking (1.535; 1.235~1.907) and drinking (1.464; 1.232~1.739). For adolescents, blood manganese was positively associated with LTBI. The OR and 95% CIs for each one-unit increase in the log-transformed level of blood manganese with LTBI were 9.954 (1.389~71.344). Conclusion Significant associations were observed in girls, aged≥12 years and in the non-Hispanic white population. In conclusion, total mercury is associated with an increased prevalence of LTBI among adults and positive association between blood manganese and LTBI was observed among adolescents. Further studies should be conducted to verify the results and explore potential biological mechanisms.